2005
DOI: 10.1038/sj.bjc.6602554
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and metabolism of ifosfamide in relation to DNA damage assessed by the COMET assay in children with cancer

Abstract: The degree of damage to DNA following ifosfamide (IFO) treatment may be linked to the therapeutic efficacy. The pharmacokinetics and metabolism of IFO were studied in 19 paediatric patients, mostly with rhabdomyosarcoma or Ewings sarcoma. Ifosfamide was dosed either as a continuous infusion or as fractionated doses over 2 or 3 days. Samples of peripheral blood lymphocytes were obtained during and up to 96 h after treatment, and again prior to the next cycle of chemotherapy. DNA damage was measured using the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…On this, data in the literature are inconclusive. Whereas some authors observed that induced damage with chemotherapy or radiotherapy returned to pretreatment values in a short term (27,28), other reports show the persistence of the injury in the lymphocytes (28,29). Very few publications show long followup periods.…”
Section: Discussionmentioning
confidence: 99%
“…On this, data in the literature are inconclusive. Whereas some authors observed that induced damage with chemotherapy or radiotherapy returned to pretreatment values in a short term (27,28), other reports show the persistence of the injury in the lymphocytes (28,29). Very few publications show long followup periods.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous experiments we used CP and IFF concentrations of 1 × 10 −3 m. [ 33 ] Maximum blood plasma concentrations in patients, depending on the administration route and dosing regimen, were reported to range between 80 × 10 −6 and 157 × 10 −6 m for CP [ 50–52 ] and between 75 × 10 −6 and 350 × 10 −6 m for IFF. [ 53–55 ] RTV successfully inhibited CYP3A4 at concentrations of 1 × 10 −6 m , while reported blood plasma concentrations in HIV patients were between 10 × 10 −6 and 22 × 10 −6 m. [ 56 ] Compared to the in vivo situation, our testing system required tenfold higher prodrug concentrations but a comparably low RTV concentration to obtain full CYP3A4 inhibition. These observations can be explained by the lower metabolic capacity of the in vitro system in comparison to the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage was quantified by single-cell gel electrophoresis [ 27 , 28 ]. Drug-treated cells were mixed with 0.5% low-melting-point agarose and added to microscope slides coated with 1.5% agarose.…”
Section: Methodsmentioning
confidence: 99%